2020
DOI: 10.2196/17405
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Health Mindfulness Intervention for Women With Moderate to Moderately Severe Postpartum Depressive Symptoms: Feasibility Study

Abstract: Background Approximately 20% of women suffer from postpartum depression (PPD). Due to barriers such as limited access to care, half of the women with PPD do not receive treatment. Therefore, it is critical to identify effective and scalable interventions. Traditional mindfulness programs have been effective in reducing depressive symptoms, however access remains a barrier. A self-paced mobile health (mHealth) mindfulness program may fit the lifestyle of busy mothers who are unable to attend in-pers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 65 publications
1
39
0
Order By: Relevance
“…The included studies reported that automated and interactive data collection and processing positively affected adherence [ 101 , 106 ]. The studies also showed that customizable features such as tracking stress and mood [ 109 ], visualizing personal progress, and immediate feedback positively affected adherence [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies reported that automated and interactive data collection and processing positively affected adherence [ 101 , 106 ]. The studies also showed that customizable features such as tracking stress and mood [ 109 ], visualizing personal progress, and immediate feedback positively affected adherence [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…The positive influence of passive and automated data collection, processing, and transmission was reported in 5% (5/97) of studies from the health domains NCD self-management [ 31 , 34 ], other NCDs [ 117 ], mindfulness [ 101 ], and meditation [ 106 ]. Thus, developers can increase adherence by automating repetitive tasks to reduce user burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies assessed the roles of mHealth in anxiety symptoms among pregnant women and mothers 35 36 39 40 44 46 47 50 54 61–63 73. Four studies found positive effects, six studies had mixed findings and three studies found no significant effect (GRADE certainty of evidence: low).…”
Section: Resultsmentioning
confidence: 99%
“…64 65 A few studies among the seven qualitative studies [66][67][68][69][70][71][72] lacked information on the positionality of researchers and potential bias may have risen due to the recruitment strategy. Seven mixedmethods study [73][74][75][76][77][78][79] also did not provide any information on confounding. Furthermore, online supplemental file 7 shows the results of the GRADE certainty of evidence assessment.…”
Section: Risk Of Bias and Methodological Rigour Of Included Studiesmentioning
confidence: 99%